EFEK ASAM LEMAK JENUH DAN ASAM LEMAK TAK JENUH "TRANS" TERHADAP KESEHATAN - Tuminah, Sulistyowati (Media Penelitian dan Pengembangan Kesehatan, 2009)
Consumption of saturated and trans unsaturated fat-rich diet are associated with the risk of coronary heart disease, because both of them can enhance blood LDL cholesterol level. However, actually they have a different impact on blood HDL cholesterol level. Trans unsaturated fatty acid decrease blood HDL cholesterol level, while saturated fatty acid elevate it. This different impact on blood HDL cholesterol level also cause a different effect to cardiovascular disease.   Key words : Trans Unsaturated Fatty Acid, Saturated Fatty Acid, Cardiovascular Disease